Implementation of the Accounting Cycle in the Sukowijoyo Batik Business Unit in Village-Owned Enterprises Sukowidi, Magetan Regency - Kholif, Kholif; Utomo, Priyo (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: This study aims to understand and analyze the implementation of the accounting cycle in the Batik Sukowijoyo business unit managed by the Sukowidi Village-Owned Enterprise in Magetan Regency. Design/Methodology/Approach: This study uses a descriptive-qualitative approach. Data were obtained through interviews, observations, documentation, and literature reviews. Data analysis was carried out by reducing data, presenting data, and drawing conclusions. Findings: The findings of this study indicate that the implementation of the accounting cycle in the Batik Sukowijoyo business unit is not yet organized. Recording of financial transactions is done in a very simple manner and does not meet applicable accounting standards. Several processes such as journaling, general ledger bookkeeping, balance sheet preparation, adjustments, and financial report preparation have not been fully implemented. This occurs due to the lack of workers with accounting experience and the limited technical training available. This study recommends the need for basic accounting training for Village-Owned Enterprise managers, the development of a simpler accounting system that is in accordance with existing regulations, and obtaining support from external parties such as academics or related institutions to improve financial management in the Batik Sukowijoyo business unit in the future. Research limitations/implications: The findings of this study are expected to be used as a reference by subsequent researchers. Practical implications: With the findings of this study, the Sukowijoyo Batik Business Unit is expected to be able to implement the accounting cycle in a systematic manner, making it easier for managers to record financial transactions. Originality/value: This research is an initial research conducted by researchers at the Batik Sukowijoyo Unit at the Sukowidi Village-Owned Enterprise regarding the accounting cycle. Paper type: Research paper